Closing the Gap in Proteomic Identification of Histoplasma capsulatum: A Case Report and Review of Literature - Terenzio Cosio; Roberta Gaziano; Carla Fontana; Enrico Salvatore Pistoia; Rosalba Petruccelli; Marco Favaro; Francesca Pica; Silvia Minelli; Maria Cristina Bossa; Anna Altieri; Domenico Ombres; Nikkia Zarabian; et al. (Journal of Fungi, 2023)
Histoplasmosis is a globally distributed systemic infection caused by the dimorphic fungus Histoplasma capsulatum (H. capsulatum). This fungus can cause a wide spectrum of clinical manifestations, and the diagnosis of progressive disseminated histoplasmosis is often a challenge for clinicians. Although microscopy and culture remain the gold standard diagnostic tests for Histoplasma identification, matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) has emerged as a method of microbial identification suitable for the confirmation of dimorphic fungi. However, to our knowledge, there are no entries for H. capsulatum spectra in most commercial databases. In this review, we describe the case of disseminated histoplasmosis in a patient living with HIV admitted to our university hospital that we failed to identify by the MALDI-TOF method due to the limited reference spectrum of the instrument database. Furthermore, we highlight the utility of molecular approaches, such as conventional polymerase chain reaction (PCR) and DNA sequencing, as alternative confirmatory tests to MALDI-TOF technology for identifying H. capsulatum from positive cultures. An overview of current evidence and limitations of MALDI-TOF-based characterization of H. capsulatum is also presented.